Análise do grau de utilização do planejamento de vendas e operações nas empresas brasileiras - Gonçalves, Eduardo Tofoli (2016)
The improvements in supply chain and the Brazilian market increasingly competitive makes the use of a system of sales planning tools and collaborative operations able to integrate the all supply chain and making savings and another benefits. This study aims to analyze the degree of utilization of sales and operations planning in Brazilian companies, using a combination of four key constructs: metrics and tools, processes and organization, results and degree of implementation. The literature review on this topic was done, then defined constructs for measuring the degree of utilization, prepared a quiz sent to Brazilian companies and then checked their results. The analysis shows that there is a low degree of use of sales and operations planning tools, ignorance of its sub-processes and low degree of senior management involvement.